Three-dimensional colloidal crystals: Crystallisation, deformation and grain boundaries - Orr, NHP (2021)
In this thesis, the crystallisation, deformation, and grain boundaries of three-dimensional colloidal crystals are studied in real space using confocal laser scanning microscopy, CLSM, and in reciprocal space using small angle X-ray scattering, SAXS. Two instances of crystallisation are studied, the first being crystallisation under shear induced by capillary action. Using CLSM and SAXS, we find that drawing a high volume fraction suspension of colloidal particles into a flat and narrow capillary creates a large random hexagonal close packed, RHCP, crystal with long-range orientational order over tens of thousands of colloidal particles. Subsequently, we monitor the deformation of the shear aligned crystals under a gravitational field using CLSM and SAXS. We find that at low enough crystal volume fractions, the initial single orientation of the crystal breaks apart into many crystallites and thus, form grain boundaries at their interfaces. We characterise the rotations of the crystallites during deformation and reveal the mechanism initiating the break-up of the uniform crystal orientation. We develop a method to locate and characterise grain boundaries which can measure local grain boundary misorientations and structure as well as determine the crystal structure of the grains either side. We demonstrate the method’s utility by applying it to experimental real space coordinates of colloidal particles. In particular, we consider particle coordinates obtained from an epitaxially templated colloidal Σ17 (a coincident site lattice grain boundary) bicrystal, finding a mosaic of different grain boundary types instead of only Σ17. We conclude with the second study of crystallisation: homogeneous crystal nucleation in a colloidal fluid. This time, crystallisation produces a crystal with many differently oriented grains and provides an opportunity to study grain boundaries and the misorientation structural changes of nuclei during nucleation. We examine the spatial misorientation variation during nucleation and growth to reveal changes with time. At early times, nuclei exhibit exclusively high misorientation angles, however, at late times, misorientation angles at the surface are higher than the angles within the nuclei cores. Thus, we show that nuclei exhibit structures intermediate between the liquid and the crystal structure at late times during nucleation and growth.